Phenoxymethylpenicillin Versus Amoxicillin for Infections in Ambulatory Care: A Systematic Review - Philip Lawrence Skarpeid; Sigurd Høye (MDPI AG, 2018)
Most antibiotics are prescribed in primary care, and commonly for respiratory tract infections (RTIs). Narrow-spectrum phenoxymethylpenicillin is the antibiotic of choice for RTIs in the Scandinavian countries, while broader spectrum amoxicillin is used in most other European countries. This review summarizes the knowledge of the effect of phenoxymethylpenicillin versus amoxicillin for infections treated in ambulatory care. We searched PubMed/Medline and Embase for trials comparing the clinical effect of phenoxymethylpenicillin and amoxicillin. The Norwegian Knowledge Centre for the Health Services’ checklist was used to assess risk of bias. In total, 1687 studies were identified, and 18 of these fulfilled the inclusion criteria. One additional study was found as a reference. The randomized controlled trials revealed no significant differences in clinical effect in acute sinusitis (three RCTs), GAS tonsillitis (11 RCTs) and Lyme borreliosis (two RCTs). One RCT on community-acquired pneumonia found amoxicillin to be superior, while the results were conflicting in the two RCTs on acute otitis. The results suggest that non-Scandinavian countries should consider phenoxymethylpenicillin as the treatment of choice for RTIs because of its narrower spectrum. More studies should be conducted on the clinical effect of phenoxymethylpenicillin versus amoxicillin for acute otitis and lower RTIs.